Response of Methanogens in Arctic Sediments to Temperature and Methanogenic Substrate Availability - Blake, Lynsay I. (PLoS One, 2015)
Although cold environments are major contributors to global biogeochemical cycles, comparatively little is known about their microbial community function, structure, and limits of activity. In this study a microcosm based approach was used to investigate the effects of temperature, and methanogenic substrate amendment, (acetate, methanol and H(2)/CO(2)) on methanogen activity and methanogen community structure in high Arctic wetlands (Solvatnet and Stuphallet, Svalbard). Methane production was not detected in Stuphallet sediment microcosms (over a 150 day period) and occurred within Solvatnet sediments microcosms (within 24 hours) at temperatures from 5 to 40°C, the maximum temperature being at far higher than in situ maximum temperatures (which range from air temperatures of -1.4 to 14.1°C during summer months). Distinct responses were observed in the Solvatnet methanogen community under different short term incubation conditions. Specifically, different communities were selected at higher and lower temperatures. At lower temperatures (5°C) addition of exogenous substrates (acetate, methanol or H(2)/CO(2)) had no stimulatory effect on the rate of methanogenesis or on methanogen community structure. The community in these incubations was dominated by members of the Methanoregulaceae/WCHA2-08 family-level group, which were most similar to the psychrotolerant hydrogenotrophic methanogen Methanosphaerula palustris strain E1-9c. In contrast, at higher temperatures, substrate amendment enhanced methane production in H(2)/CO(2) amended microcosms, and played a clear role in structuring methanogen communities. Specifically, at 30°C members of the Methanoregulaceae/WCHA2-08 predominated following incubation with H(2)/CO(2), and Methanosarcinaceaeand Methanosaetaceae were enriched in response to acetate addition. These results may indicate that in transiently cold environments, methanogen communities can rapidly respond to moderate short term increases in temperature, but not necessarily to the seasonal release of previously frozen organic carbon from thawing permafrost soils. However, as temperatures increase such inputs of carbon will likely have a greater influence on methane production and methanogen community structure. Understanding the action and limitations of anaerobic microorganisms within cold environments may provide information which can be used in defining region-specific differences in the microbial processes; which ultimately control methane flux to the atmosphere.